Multiple plant growth-promoting traits of selective endophytic bacteria from Plectranthus hijazensis in Shada Al-Asfal Mountain - Alzahrani, Kholoud; Jastaniah, Samyah; Aly, Magda (Bangladesh Journal of Botany, 2025)
This work was aimed to isolate and screen endophytic bacteria from Plectranthus hijazensis, collected from Shada Alasfal Mountain, Saudi Arabia, and study their roles in the plant growth-promotion. The results showed that they could produce HCN, ammonia, IAA, and some hydrolytic enzymes. Based on these results, the selected endophytic bacteria as efficient plant growth promoters could be chosen and used as efficient bacteria for future greenhouse and field experiments. Bangladesh J. Bot. 54(1): 61-66, 2025 (March)